2018
DOI: 10.1016/j.freeradbiomed.2018.05.075
|View full text |Cite
|
Sign up to set email alerts
|

Selenoproteins in colon cancer

Abstract: Selenocysteine-containing proteins (selenoproteins) have been implicated in the regulation of various cell signaling pathways, many of which are linked to colorectal malignancies. In this in-depth excurse into the selenoprotein literature, we review possible roles for human selenoproteins in colorectal cancer, focusing on the typical hallmarks of cancer cells and their tumor-enabling characteristics. Human genome studies of single nucleotide polymorphisms in various genes coding for selenoproteins have reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 194 publications
0
51
0
Order By: Relevance
“…A study in Japan showed that GPX1, GPX3 and SELENOP were decreased and GPX2 was increased in colorectal cancer (CRC) ( 22 ). A study reviewed by Peters et al found that the redox homeostasis related selenoproteins GPX1-4, TXNRD1, SELENOF and SELENOP, and the WNT/β-catenin signalling pathway associated selenoproteins DIO3, GPX2, TXNRD3 and SELENOP may effect CRC risk and development ( 23 ). To the best of our knowledge, there are many selenoproteins whose roles in CRC are unknown ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study in Japan showed that GPX1, GPX3 and SELENOP were decreased and GPX2 was increased in colorectal cancer (CRC) ( 22 ). A study reviewed by Peters et al found that the redox homeostasis related selenoproteins GPX1-4, TXNRD1, SELENOF and SELENOP, and the WNT/β-catenin signalling pathway associated selenoproteins DIO3, GPX2, TXNRD3 and SELENOP may effect CRC risk and development ( 23 ). To the best of our knowledge, there are many selenoproteins whose roles in CRC are unknown ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study reviewed by Peters et al found that the redox homeostasis related selenoproteins GPX1-4, TXNRD1, SELENOF and SELENOP, and the WNT/β-catenin signalling pathway associated selenoproteins DIO3, GPX2, TXNRD3 and SELENOP may effect CRC risk and development ( 23 ). To the best of our knowledge, there are many selenoproteins whose roles in CRC are unknown ( 23 ). These observations indicate that the selenoproteomes which exhibited significant changes in this study are a promising research target, which should have high priority.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Both Se-containing compounds and the Se atom present in the active sites of 25 mammalian selenoproteins identified so far participate in key cellular and physiological processes, as well as diseases such as cancer, inflammation, immunity, type 2 diabetes or liver diseases. [3][4][5][6][7][8] However, the molecular mechanism of action is not fully understood yet for some of these selenoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies relating selenium supplementation with immune response, using tumors as a model, have shown that this nutrient in many cases can reduce or inhibit tumor growth, both in humans an rodent models 14,15 . Decreased in incidence of cancer by selenium intake has been shown in epidemiological studies in humans and other animals with selenium supplementation showed a reduction in tumor incidence or tumor size.…”
Section: Regression Of Bph After Decreasing Of Androgens Serum Levelsmentioning
confidence: 99%